Post-Crisis Growth in Developing Countries : A Special Report of the Commission on Growth and Development on the Implications of the 2008 Financial Crisis - Commission on Growth and Development (Washington, DC: World Bank, 2013)
In May 2008, the Commission released the growth report: strategies for sustained growth and inclusive development. At that time, the financial systems of the United States and Europe were under stress. Commodity prices were also spiking, posing particular difficulties for developing countries because of the impact on the poor and on potential future inflation. But no one foresaw the full magnitude of the crisis that erupted in the fall of 2008, more than a year ago. The crisis was a destructive malfunction of the financial sectors of the advanced economies, which spread rapidly to the real economy and to the rest of the globe. Even countries far from the source of the crisis had to cope with capital volatility, tight credit, and rapidly falling trade. At the request of several members of the Commission, Commission held a workshop on the crisis and its implications for developing countries. Commission followed standard procedure of asking for help and insight from a distinguished group of scholars, analysts, and practitioners. This report is an outgrowth of that process. It is an attempt to look at the crisis and its aftermath from the point of view of developing countries. Commission wanted to assess the impact of these events, and determine if the growth strategies recommended needed major revision, or some adaptive fine tuning. Commission also wanted to think more carefully about resilience, and what it might mean for successful sustained growth. The report that follows is a summary of thinking on these and related questions.